Aquatic Macroinvertebrates of Arid and Semi-Arid Ecosystems of Peru - Arana Maestre, Jerry; Carrasco Badajoz, Carlos; Coayla Peñaloza, Pastor; Rayme Chalco, Carolina; Sánchez Peña, Marco (Frontiers in Environmental Science, 2021)
Peru is one of the megadiverse countries worldwide, displaying a great diversity of ecosystems due to its tropical location, marine currents, and complex relief, which jointly define environments differentiated by altitude and climatic conditions. The arid and semi-arid ecosystems comprising xeric and Andean shrublands, coastal deserts, and coastal hills, illustrate this diversity of ecosystems; these stretch over 177 358 km2, representing 13.8% of the Peruvian territory. Several studies on aquatic macroinvertebrates are being conducted in these ecosystems; although not so numerous yet, have shown a rise in recent years. The objective of this work was to determine the composition and distribution of aquatic macroinvertebrates in the arid and semi-arid ecosystems of Peru. To this end, we conducted a literature survey; the articles and theses found were reviewed and analyzed. The following keywords were used: macroinvertebrates, macrozoobenthos, bioindicators, diversity of aquatic organisms, and water quality; we used the Google Academic search engine, Scopus, Web of Science, ResearchGate and the thesis repositories of Peruvian universities, additionally a thesis from the University of Barcelona. Of a total of 53 sources of information, 38 are theses and 15 are scientific articles conducted from 1992 to 2020, referring to studies conducted at elevations ranging from 0 to 3,831 m asl. Most studies were conducted at the Lima and La Libertad departments, resulting in 20 and 10 publications, respectively. The topics addressed most frequently were bioindication, biodiversity, taxonomy, and distribution. Most theses were carried in the Universidad Nacional de Trujillo and the Universidad Nacional Mayor de San Marcos, with 12 and 10 theses, respectively. The period 2011–2020 records the largest number of publications (40). According to the type of aquatic ecosystem, rivers (38) were the systems most intensively studied, followed by coastal wetlands (14) and lagoons (2); to note, one thesis studied two types of ecosystems. Specimens were collected mainly with the Surber and D nets; as a result, seven phyla, 10 classes, 39 orders, and 118 families were reported. The highest richness of families corresponds to rivers (110), followed by coastal wetlands (57), and lagoons (12). The western hydrographic slope recorded the highest richness at phylum, class, order, and family levels, likely because most investigations were conducted in this slope. On the other hand, the phyla Cnidaria, Nematoda, and Nematomorpha were not recorded in the eastern slope, which showed fewer orders (19) relative to the western slope (39). A similar trend is observed at the family level: of the 118 families recorded, 59 were reported for the eastern slope. The most common families at both sides were Chironomidae, Baetidae, Simuliidae, Elmidae, Hydrophilidae, Libellulidae, Physidae, Dytiscidae, Ceratopogonidae, Coenagrionidae, Hydroptilidae, Hydropsychidae, and Tipulidae. Separately, the most common families in all types of aquatic ecosystems were Chironomidae, Baetidae, and Dytiscidae. It is recommended to further promote studies on macroinvertebrates living in the eastern slope, addressing taxonomic, and ecological topics, as well as broadening the approach to an integral ecosystem view. Finally, the biotic indices should be calibrated and validated for the main hydrographic basins. This work is an initial effort to review, systematize, analyze, and gather the results of studies on aquatic macroinvertebrates in Peru, particularly in arid and semi-arid ecosystems.